2015
DOI: 10.1002/jaba.229
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and distal effects of the good behavior game

Abstract: The Good Behavior Game (GBG) has been demonstrated to reduce disruptive student behavior during implementation. The effects of playing the GBG on disruption immediately before and after the GBG are unknown. The current study evaluated the effects of the GBG on disruption in 5 kindergarten classes immediately before, during, and after GBG implementation. The GBG reduced disruption during implementation but did not affect rates of disruption during activity periods that preceded or followed the GBG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 11 publications
5
27
0
1
Order By: Relevance
“…In Classroom 2, we provided a demonstration of the effects of the GBG on student and staff behavior in the same classroom at different times in the school day. Results were consistent with Donaldson, Wiskow, and Soto (), who found that the GBG reduced disruption when implemented but did not influence rates of disruption during an activity period that directly followed the GBG. That is, implementing the GBG in the AM class did not have a pronounced effect on student or staff behavior in the PM class.…”
Section: Discussionsupporting
confidence: 88%
“…In Classroom 2, we provided a demonstration of the effects of the GBG on student and staff behavior in the same classroom at different times in the school day. Results were consistent with Donaldson, Wiskow, and Soto (), who found that the GBG reduced disruption when implemented but did not influence rates of disruption during an activity period that directly followed the GBG. That is, implementing the GBG in the AM class did not have a pronounced effect on student or staff behavior in the PM class.…”
Section: Discussionsupporting
confidence: 88%
“…Following a slight delay, a decrease in both variability and level of disruptive behavior occurred every time the experimenter implemented the GBG. These results replicate results of previous research evaluating the GBG with young children (Donaldson et al, ; Donaldson et al, ; McGoey et al, ; Tanol et al, ) while extending the generality of the intervention to a new population and setting (i.e., preschoolers in a structured learning activity). Given that research suggests that problem behavior originating in the preschool years persists over time (Breitenstein, Hill, & Gross, ; Del'Homme et al, ) and is associated with poor academic outcomes in subsequent school years (Bulotsky‐Shearer & Fantuzzo, ), preschool administrators should consider using the GBG to address problem behavior occurring in these early years.…”
Section: Discussionsupporting
confidence: 87%
“…We selected scented lip balms as the reward for several reasons. First, we observed the effectiveness of using these scents with kindergarten students in a previous study (e.g., Donaldson, Wiskow, & Soto, ). Second, students emitted statements suggesting the scents were preferred (e.g., “I want orange!” “Smell mine!”).…”
Section: Methodsmentioning
confidence: 89%